Agonism of 4-1BB for immune therapy: a perspective on possibilities and complications - Salek-Ardakani, Shahram; Zajonc, Dirk M.; Croft, Michael (Frontiers in Immunology, 2023)
Costimulatory receptors on immune cells represent attractive targets for immunotherapy given that these molecules can increase the frequency of individual protective immune cell populations and their longevity, as well as enhance various effector functions. 4-1BB, a member of the TNF receptor superfamily, also known as CD137 and TNFRSF9, is one such molecule that is inducible on several cell types, including T cells and NK cells. Preclinical studies in animal models have validated the notion that stimulating 4-1BB with agonist reagents or its natural ligand could be useful to augment conventional T cell and NK cell immunity to protect against tumor growth and against viral infection. Additionally, stimulating 4-1BB can enhance regulatory T cell function and might be useful in the right context for suppressing autoimmunity. Two human agonist antibodies to 4-1BB have been produced and tested in clinical trials for cancer, with variable results, leading to the production of a wealth of second-generation antibody constructs, including bi-and multispecifics, with the hope of optimizing activity and selectivity. Here, we review the progress to date in agonism of 4-1BB, discuss the complications in targeting the immune system appropriately to elicit the desired activity, together with challenges in engineering agonists, and highlight the untapped potential of manipulating this molecule in infectious disease and autoimmunity.